A literature review: The comparison of the sedimentation and flotation technique for Fasciola hepatica detection in livestok - Alisa Qudrotun Munawaroh; Endry Nugroho Prasetyo; Maharani Pertiwi Koentjoro (Litbang PWM Jawa Tengah, 2021)
Fascioliasis is an infection of the trematodes of Fasciola hepatica and Fasciola gigantica which causes disease worldwide. This trematode infection commonly attacks ruminants, especially in cattle, buffalo, sheep, goats, pigs and humans, as well. This disease can cause significant economic losses in the livestock industry, mainly through death, liver damage, reduced production of meat, milk and wool, and expenses for deworming. Parasitological examination for identification of fasciola infection was carried out by visually observing fecal samples for adult worms and then examined by simple flotation (using saturated NaCl solution) and formalin-ethyl acetate sedimentation techniques. Here, we were systematically reviewed existing knowledge about sensitive and efficient fasciola observation methods for the identification of fasciola species. Four databases of articles that met the inclusion requirements were compiled for the literature review. This article was published between 2015-2020 and reports on the identification of fasciola species using one or a combination of sedimentation and flotation methods. As a result, the combined method of sedimentation and flotation has the best sensitivity and egg recovery rate (Ef) values for fasciola identification. Abstrak Fascioliasis merupakan infeksi trematoda spesies Fasciola hepatica dan Fasciola gigantica yang menimbulkan penyakit di seluruh dunia. Infeksi trematoda ini umum menyerang ruminansia, terutama pada sapi, kerbau, domba, kambing, babi dan bisa terjadi pada manusia. Penyakit ini dapat menimbulkan kerugian ekonomi yang cukup besar dalam industri ternak, terutama melalui kematian, kerusakan hati, berkurangnya produksi daging, susu, dan wol, dan pengeluaran biaya untuk obat cacing. Pemeriksaan parasitologi untuk identifikasi infeksi fasciola dilakukan dengan mengamati sampel feses secara visual untuk cacing dewasa dan kemudian diperiksa dengan cara flotasi sederhana (menggunakan larutan NaCl jenuh) dan teknik sedimentasi formalin-etil asetat. Disini, kami meninjau secara sistematis pengetahuan yang ada tentang metode pengamatan fasciola yang sensitif dan efisien dalam identifikasi spesies fascioal. Empat data base artikel yang telah memenuhi syarat inklusi disusun untuk tinjauan literature review. Artikel ini terbit antara tahun 2015-2020 dan melaporkan identifikasi spesies fasciola menggunakan salah satu atau gabungan metode sedimentasi dan flotasi. Hasilnya, metode gabungan antara sedimentasi dan flotasi memiliki nilai sensitivitas dan nilai tingkat pemulihan telur (egg recovery rate, Ef) paling baik untuk identifikasi fasciola.